2022
DOI: 10.3390/horticulturae8060539
|View full text |Cite
|
Sign up to set email alerts
|

Quantitatively Unravelling the Impact of High Altitude on Oolong Tea Flavor from Camellia sinensis Grown on the Plateaus of Tibet

Abstract: The plateaus of Tibet have a unique climate that poses a great challenge for local agriculture. To promote sustainable development in Tibet, an elite tea variety has been introduced. However, the modifications of tea flavors in response to the climate of the plateaus are unknown. In this study, volatile organic compounds (VOCs) and other taste substances of tea planted in its original location (OOT) and in Tibet (TOT) were systematically analyzed and compared. The volatile components in TOT and OOT showed a sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Water-extractable substances are soluble substances extracted from tea leaves using boiling water under defined conditions [ 45 ]. The main substances in the water-extractable, including polyphenols such as caffeine, catechins, and free amino acids determine the consistency and taste of the tea infusion and are considered to be one of the most important indicators of tea quality [ 46 ]. We found that in the white peony tea group, there were no significant differences in the content of water-extractable substances between SP and AP.…”
Section: Resultsmentioning
confidence: 99%
“…Water-extractable substances are soluble substances extracted from tea leaves using boiling water under defined conditions [ 45 ]. The main substances in the water-extractable, including polyphenols such as caffeine, catechins, and free amino acids determine the consistency and taste of the tea infusion and are considered to be one of the most important indicators of tea quality [ 46 ]. We found that in the white peony tea group, there were no significant differences in the content of water-extractable substances between SP and AP.…”
Section: Resultsmentioning
confidence: 99%
“…Headspace solid-phase microextraction (HS-SPME) was used to extract the volatile components of tea leaves [ 2 ]. The DT and FLs were ground into a fine powder in a mortar and pestle using liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…FHDC stands out for its unique aroma and diverse fragrance profiles, which are shaped by factors such as its cultivar, manufacturing processes and environmental conditions [ 2 , 3 , 4 ]. Harsh conditions like low humidity, intense light and dry heat in summer and autumn often degrade the quality of tea leaves [ 1 , 5 ], while the mild temperatures and high humidity of spring enhance it.…”
Section: Introductionmentioning
confidence: 99%
“…Identification and quantification of volatiles were performed with headspace gas chromatography as in Chen et al [31] using an Agilent 1890B gas chromatograph and a 5977A mass spectrometer (Agilent, Santa Clara, CA, USA) with an HP-5 MS column (30 m × 0.25 mm × 0.25 µm film thickness). A solid-phase microextraction device consisting of divinylbenzene/carboxylic acid/polydimethylsiloxane (DVB/CAR/PDMS) fibers (50/30 µm inner diameter, 2 cm length; Supelco, Darmstadt, Germany) was inserted into headspace vials and compounds were extracted at 80 • for 40 min.…”
Section: Gc-ms Analysis Of Volatile Compoundsmentioning
confidence: 99%
“…where RT(x) is the retention time of compound x and RT(n) and RT(n + 1) are the retention times of alkanes with carbon numbers n and n + 1 that immediately preceded and followed the elution of the compound [31].…”
Section: Gc-ms Analysis Of Volatile Compoundsmentioning
confidence: 99%